Big no depression: Flipbook-based brain gym innovation to prevent depression in teenagers - Cantika, Rindi Dwi; Mawddah, Nahdah Tunnisah; Lestari, Nur Khafifah; Ningsih, Nurwidya; Wijaya, Dian Rezki (Sociality: Journal of Public Health Service, 2024)
Indonesia has taboo thoughts about mental health, public indifference to mental health causes people with mental disorders to tend to shut themselves down and be ashamed. Seeing that the increase continues to occur, the service carries out an effort to prevent depression, namely Brain Gym Innovation. The aim of this intervention is to improve the knowledge and understanding of adolescents on UINAM Public Health's new knowledge of Brain Gym Innovation. Based on Flipbook as a depression prevention strategy. As for the description of the activities in this intervention by determining the origin of the problem with the ultrasound method and obtaining mental health as the priority that the intervention wants to be performed. The target of this activity was Department of Public Health freshman, FKIK UINAM which was held in the classrooms of AB campus 2 UINAM on Monday 11 December 2023 where the target activity was at least 20 people who attended this extension activity. The results obtained on the service carried out that the level of knowledge and understanding in the new students improved, where health extension related to brain gym innovation was carried out and pre-test & post-test measurements were carried out. states that the majority of students have a level of leadership with good categories. Therefore, it can be concluded that the health extension Brain Gym Innovation based on Flipbook has an influence on the level of knowledge of the respondents.